EPCT-02. PBTC-051: FIRST IN PEDIATRICS PHASE 1 STUDY OF CD40 AGONISTIC MONOCLONAL ANTIBODY APX005M IN PEDIATRIC SUBJECTS WITH RECURRENT/REFRACTORY BRAIN TUMORS. (4th December 2020) - Lindsay, Holly; Onar-Thomas, Arzu; Kocak, Mehmet; Poussaint, Tina Young; Dhall, Girish; Broniscer, Alberto; Vinitsky, Anna; MacDonald, Tobey; Trifan, Ovid; Fangusaro, Jason; Dunkel, Ira
Abstract: BACKGROUND: CD40 is a co-stimulatory molecule expressed on antigen presenting cells (APCs). APX005M is a CD40 agonist monoclonal antibody which stimulates innate and adaptive anti-tumor immunity through activation of APCs, macrophages, and antigen-specific CD8 + T-cells. Pediatric Brain Tumor Consortium study PBTC-051 is the first investigation of APX005M in pediatric patients and is evaluating the safety, recommended phase 2 dose (RP2D), pharmacokinetics, and preliminary efficacy of APX005M in children with central nervous system (CNS) tumors. RESULTS: Accrual of patients with recurrent/refractory primary malignant CNS tumors (stratum 1) began in March 2018. 16 patients (2 ineligible) have enrolled on this stratum; 14 were treated. Dose escalation through 3 planned dose levels of APX005M was completed without excessive or unanticipated toxicities. The highest dose level (0.6 mg/kg q3 weeks) is the presumptive RP2D, and an expansion cohort is currently enrolling at this dose. 2 patients at dose level 3 have received >12 cycles of therapy. Grade 3 or higher adverse events at least possibly attributable to APX005M include 11 lymphopenia, 5 neutropenia, 5 leukopenia, 3 ALT elevations, 1 AST elevation, 1 thrombocytopenia, and 1 hypoalbuminemia. PK data will be available March 2020. Stratum 2 is now enrolling patients with post-radiation/pre-progression DIPG beginning at dose level 2, with 1 patient currently enrolled. CONCLUSION: The CD40 agonistic antibody APX005M has demonstrated preliminary safety in pediatric patients with recurrent/refractory primary malignant CNS tumors and has a likely RP2D of 0.6 mg/kg q3 weeks in this population. Preliminary efficacy data are pending.